Phenomenology Study: Occupational Diseases and Accidents in Nurses in Coastal and Border Areas - Yulis, Rahma; Fitri, Gusni; Fitriani, Fitriani (Jurnal Berita Ilmu Keperawatan, 2025)
Nurses are health workers who are at high risk of experiencing occupational diseases and accidents. The purpose of this study was to obtain an overview of the experiences of nurses in coastal and border areas who have experienced occupational diseases or accidents. This study used a qualitative design with a phenomenological method. Participants were selected using purposive sampling techniques of 9 nurses from different rooms. Data were collected using in-depth interviews related to experiences. 7 themes were identified in this study, namely: 1)Implementing Occupational Health and Safety is Important to Maintain the Safety of Yourself and Others. 2) Nurses experience more than one type of occupational disease or accident during work. 3) Unsafe acts and conditions are the causes of occupational diseases and accidents. 4) Nurses’ initial response when experiencing occupational diseases or accidents. 5) Changes felt by nurses after experiencing occupational diseases and accidents. 6) Efforts to prevent occupational diseases and accidents by nurses and hospital management. 7) Nurses need Hospital Management support to maintain their Occupational Health and Safety. Conclusion: occupational diseases and accidents can be caused by the negligence of nurses themselves, co-workers, patients, and patient companions, the lack of managerial roles, and an unsafe environment. Experience of work accidents causes physical and psychological discomfort in nurses which can be temporary or long-term. Therefore, support from all parties is needed to maintain Occupational Health and Safety for nurses.